1996
DOI: 10.1111/j.1525-1446.1996.tb00233.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Perceived Benefits of and Barriers to Reported Exercise in Older African American Women

Abstract: The purpose of this descriptive study was to determine the perceived benefits of and barriers to exercise of a convenience sample of older African American women in senior citizen centers in an urban area in the mid-South. This descriptive study utilized a convenience sample of older African American women over 60 years of age and examined the relationship among their current exercise levels, their perceptions regarding the importance of exercise, and the benefits of and barriers to engaging in regular exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
1
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 22 publications
4
66
1
2
Order By: Relevance
“…African American women were convinced of the utility of physical activity; a concern with disease prevention and the consequences of ill health was an expressed value of knowledge regarding physical activity. Jones and Nies (1996) found that African American women who perceived exercise to be beneficial and perceived few barriers to exercise engaged more frequently in activity. Statements of perceived benefit related to physical activity included feelings of decreased stress, enhanced physical performance, and increased social interaction.…”
Section: Intrapersonal Resourcesmentioning
confidence: 96%
See 3 more Smart Citations
“…African American women were convinced of the utility of physical activity; a concern with disease prevention and the consequences of ill health was an expressed value of knowledge regarding physical activity. Jones and Nies (1996) found that African American women who perceived exercise to be beneficial and perceived few barriers to exercise engaged more frequently in activity. Statements of perceived benefit related to physical activity included feelings of decreased stress, enhanced physical performance, and increased social interaction.…”
Section: Intrapersonal Resourcesmentioning
confidence: 96%
“…In qualitative studies of physical activity and self-perceived health status, poor health is often cited as a barrier to participation in physical activity. Fatigue from exercise and the perceptions of exercise as "hard work" among African American women has been identified as a significant barrier to regular activity, which may reflect changes in functional status with age as well as the demands of required activities during the day (Ainsworth, Wilcox, Thompson, Richter, & Henderson, 2003;Jones & Nies, 1996;Nies, Vollman, & Cook, 1999). Eyler et al (1998) found that health concerns, primarily those related to chronic illness, were prevalent barriers to regular physical activity among minority women.…”
Section: Intrapersonal Resourcesmentioning
confidence: 97%
See 2 more Smart Citations
“…Jones and Nies (1996) conducted a study to determine the barriers perceived by African American women over 60 years of age. They found that exercise availability and accessibility were the most critical issues.…”
Section: Socioeconomic Barriers To Exercisementioning
confidence: 99%